Mechanisms Responsible for the Trophic Effect of Beta-Adrenoceptors on the Ito Current Density in Type 1 Diabetic Rat Cardiomyocytes - Raúl Setién; Aintzane Alday; Cristina Diaz-Asensio; Janire Urrutia; Mónica Gallego; Oscar Casis (Cellular Physiology and Biochemistry, 2013)
Background/Aims: In diabetic ventricular myocytes, transient outward potassium current (Ito) amplitude is severely reduced because of the impaired catecholamine release that characterizes diabetic autonomic neuropathy. Sympathetic nervous system exhibits a trophic effect on Ito since incubation of myocytes with noradrenaline restores current amplitude via beta-adrenoceptor (βAR) stimulation. Here, we investigate the intracellular signalling pathway though which incubation of diabetic cardiomyocytes with the βAR agonist isoproterenol recovers Ito amplitude to normal values. Methods: Experiments were performed in ventricular myocytes isolated from streptozotocin-diabetic rats. Ito current was recorded by using the patch-clamp technique. Kv4 channel expression was determined by immunofluorescence. Protein-protein interaction was determined by coimmunoprecipitation. Results: Stimulation of βAR activates first a Gαs protein, adenylyl cyclase and Protein Kinase A. PKA-phosphorylated receptor then switches to the Gαi protein. This leads to the activation of the βAR-Kinase-1 and further receptor phosphorylation and arrestin dependent internalization. The internalized receptor-arrestin complex recruits and activates cSrc and the MAPK cascade, where Ras, c-Raf1 and finally ERK1/2 mediate the increase in Kv4.2 and Kv4.3 protein abundance in the plasma membrane. Conclusion: β2AR stimulation activates a Gαs and Gαi protein dependent pathway where the ERK1/2 modulates the Ito current amplitude and the density of the Kv4.2 and Kv4.2 channels in the plasma membrane upon sympathetic stimulation in diabetic heart.